Adaptations within female US Olympic swimming medalists` competition-day routines: A mixed-methods approach - Grant, M. A.; Schempp, P. G.; Grant, J. T. (International Journal of Sports Science & Coaching, 2024)
The purpose of this study was to examine adaptations within competition day routines of female US Olympic medalists in differently formatted competitions in order to locate changes based on the organizations of the swimming competitions and differentiate the inflexible from the flexible parts of the routines. A purposeful sample of six elite swimmers participated in two 1-hour interviews with an observation at a national-level competition. A mixed-methods analysis protocol helped locate adaptions within the routine. Four results of note were reported. First, adaptations outside venue depended on format and/or individual schedule; adaptations inside the venue were in response to how they felt and their surroundings. Second, participants adapted their competition-day routines at different levels, i.e., segment and behavior levels, depending on being outside or inside the venue, respectively. Third, the competition-day routine of the participants followed similar competition-day routine segments at the venue that matched in scope and sequence for both the prelims and finals sessions. Fourth, once at the venue, adaptation of behaviors changed in order to accomplish the necessary active or passive preparations without changing the scope, sequence and duration of the segments. These findings deepen the understanding of competition-day routines by locating flexible and inflexible parts of the routines and showing greater variance when athletes adapt their routines.